PENINGKATAN HASIL BELAJAR SISWADALAM PEMBELAJARAN IPS DENGAN PENGGUNAAN PENDEKATAN KONSTRUKTIVIS - Sari, Desi Purnama (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The purpose of this research is to describe the fourth grade student achievement in the lesson of IPS by using construktivis approach. The research was applied in fifth grade of SDN 08 Maek with 21 student. It used quality and quantity approachment with classroom action research (PTK). The research had done in two cycles.Constructivis approach with 5 step.The sourch is also connected with lesson plan and the result of learning. Kata kunci : hasil belajar, mata pelajaran IPS, pendekatan konstruktivis